Benzene and NOx photocatalytic-assisted removal using indoor lighting conditions. (April 2022) - Tobaldi, David Maria; Dvoranová, Dana; Lajaunie, Luc; Czikhardtová, Kristina; Figueiredo, Bruno; Calvino, José Juan; Seabra, Maria Paula; Labrincha, João António
Abstract: Modern life-style is creating an indoor generation : human beings spend approximately 90% of their time indoors, almost 70% of which is at home – this trend is now exacerbated by the lockdowns/restrictions imposed due to the COVID-19 pandemic. That large amount of time spent indoors may have negative consequences on health and well-being. Indeed, poor indoor air quality is linked to a condition known as sick building syndrome. Therefore, breathing the freshest air possible is of outmost importance. Still, due to reduced ventilation rates, indoor air quality can be considerably worse than outdoor. Heating, ventilation, and air conditioning (HVAC), air filtration systems and a well-ventilated space are a partial answer. However, these approaches involve only a physical removal. The photocatalytic mineralization of pollutants into non-hazardous, or at least less dangerous compounds, is a more viable solution for their removal. Titanium dioxide, the archetype photocatalytic material, needs UVA light to be 'activated'. However, modern household light emitting diode lamps irradiate only in the visible region of the solar spectrum. We show that the surface of titanium dioxide nanoparticles modified with copper oxide(s) and graphene has promise as a viable way to remove gaseous pollutants (benzene and nitrogen oxides) using a common light emitting diode bulb, mimicking real indoor lighting conditions. Titanium dioxide, modified with 1 mol% Cu x O and 1 wt% graphene, proved to have a stable photocatalytic degradation rate, three times higher than that of unmodified titania. Materials produced in this research work are thus strong candidates for offering a safer indoor environment. Graphical abstract: Image 1 Highlights: Photocatalytic removal of a hazardous volatile organic compound and nitrogen oxides with a households white light emitting diode. Copper oxides allow for vis-light absorption. Graphene grants a spatial charge separation of the photogenerated exciton. complex and dynamic system upon light excitation is confirmed using electron paramagnetic resonance spectroscopy. TiO2 hybridization with only 1.0 wt% graphene & 1.0 mol% Cu x O was the optimum .